The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2196/12324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Full Body Exergaming in Virtual Reality on Cardiovascular and Muscular Parameters: Cross-Sectional Experiment

Abstract: Background In recent years, many studies have associated sedentary behavior in front of screens with health problems in infants, children, and adolescents. Yet options for exergaming—playing video games that require rigorous physical exercise—seem to fall short of the physical activity levels recommended by the World Health Organization. Objective The purpose of this study was to investigate the effect of a fully immersive virtual reality (VR)-based tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 59 publications
2
11
0
3
Order By: Relevance
“…VR systems can offer to people a refreshing and enjoyable form of physical activity. In prevention and therapy, the quality of movement is a fundamental component of an effective resistance training for the benefit of health (Feodoroff, 2019). Virtual reality (VR) can simulate visuospatial environments where patients could practice in total safety and with results similar to classic treatments (Aria, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…VR systems can offer to people a refreshing and enjoyable form of physical activity. In prevention and therapy, the quality of movement is a fundamental component of an effective resistance training for the benefit of health (Feodoroff, 2019). Virtual reality (VR) can simulate visuospatial environments where patients could practice in total safety and with results similar to classic treatments (Aria, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…We should increase the currently small number of reference publications in the motor field of VR technology, taking advantage of the critical issues that have emerged from previous studies. For example, trying to involve as many subjects as possible (Weber, 2019) for the study sample and for the control group that in some cases was absent (Vourvopoulos, 2019), taking advantage of the high involvement of the participants through immersive motor play activities (Feodoroff, 2019). In addition, it has been found that increasing the duration of sessions could lead to greater benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, given the potential of IVR games to improve physical conditioning and strength, and the fact that they are programmed and designed to take into account the scientific recommendations that govern physical training [8] , the aim of this study was to analyze the effect of IVR training compared to conventional training on conditioning and quality of life of sedentary university students in both the short and long term.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, scientific studies have recently started to recognize the potential positive impact of virtual reality video games on people's health (eg, [16,17]) and cognitive abilities (eg, [18,19]). For example, a previous study [18] has reported the efficacy of a virtual reality exercise-based dance game, DANCE, that was created ad hoc by researchers for the training of executive functions in older people.…”
Section: Introductionmentioning
confidence: 99%